COMPARISON BETWEEN COMPUTED TOMOGRAPHY, FLUOROSCOPY, AND ULTRASONOGRAPHY FOR GUIDING PERCUTANEOUS INJECTION OF THE CANINE INTERVERTEBRAL DISC. Issue 5 (12th March 2014) - MacKenzie, Shawn D.; Caswell, Jeff L.; Brisson, Brigitte A.; Gaitero, Luis; Chalmers, Heather J.
<x xml:space="preserve">Abstract</x> A minimally invasive method for delivering injectable therapeutic agents would be desirable for the treatment of intervertebral disc disease in dogs. The purpose of this study was to compare computed tomography (CT), ultrasonography (US), and fluoroscopy modalities for guiding percutaneous injection into canine intervertebral discs. Intervertebral discs of 14 dog cadavers were injected with a gelified ethanol therapeutic agent. Successful injectate placement and injectate leakage were determined based on necropsy inspection of discs. Injection into the nucleus pulposus was successful in 55 of 78 (71%) of all injected discs. Injections guided using CT and fluoroscopy were significantly more successful than US‐guided injections. Odds of successful injection without leakage were greater for CT vs. US (P = 0.0026) but there was no significant difference between CT and fluoroscopy (P = 0.0620). Injection success rates did not differ among vertebral sites or dog cadavers of varying weights. Forty‐nine (63%) of injection sites had injectate leakage outside the disc and 10 of these involved structures within the vertebral canal. The highest rate of injection success with the least amount of leakage was achieved with CT guidance. Findings indicated that CT, fluoroscopy, and US are feasible modalities for guiding percutaneous injection of a gelified ethanol therapeutic agent into the canine intervertebral disc, with moderate to high success rates for different regions of the spine. However, a moderately high rate of injectate leakage occurred outside of the disc and this should be taken into consideration for future safety and efficacy studies.